CPB-ARM -- A New Code Compression Method for Embedded Systems - Dias, Wanderson Roger Azevedo; Moreno, Edward David (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2012: Anais do XIII Simpósio em Sistemas Computacionais de Alto Desempenho, 2012)
In the design of embedded systems, memory is one of the most restricted resources. The code compression has been proposed as a solution to reduce the code size of applications that run on embedded systems. However, one major challenge is to develop an efficient compression technique that generates a substantial reduction in code size without affecting the overall system performance. We have observed that most previous work compresses only instruction individually. Therefore, this paper proposes a new code compression method (CPB-ARM) which comprises four different types of compression techniques, and each of these techniques form different patterns of blocks taking into account the class and the format of each instruction. The simulation results showed that our method, which uses only 18 instructions, the most frequently used by the application, obtained a compression ratio of approximately 24% for twenty MiBench applications.